Akuntansi Sederhana Bagi Usaha Rumah Tangga Pengolahan Buah Mangrove di Kabupaten Mempawah - Dewi Kurniati; Eva Dolorosa; Nurliza Nurliza (Institut Pertanian Bogor, 2020)
Mangrove fruits can be used as an alternative food stuffs. Household businesses in Mempawah Regency processed mangrove fruits into products in the form of dodol, syrup, and flour. Nevertheless, the processing done by the community was very simple and required a long time. One disadvantage of household businesses in managing their businesses was the poor financial management, specifically related to the accounting bookkeeping process. This service activity aimed to provide accounting training for household businesses so that they can have better financial management knowledge and procedures. The method used was the accounting training practice. This training activity was participated in by the mangrove fruit processing household business operators which was carried out in Sungai Bakau Besar Laut Village, Siliki Pinyuh Sub-district, Mempawah District. The results of the training showed an increase in the knowledge and abilities of the participants in accounting bookeeping and the participants practiced themselves in their respective businesses. To support the sustainability of this training program, a mentoring program from the government and academia are needed.